Perivascular Epithelioid Cell Tumor (PEComa) of the Sigmoid Colon: Case Report and Literature Review - Gintare Slice; Rokas Stulpinas; Tomas Poskus; Marius Kryzauskas (Current Oncology)
Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal neoplasms characterized by perivascular epithelioid cell proliferation. They can occur in various organs, but colonic PEComas are exceptionally rare, showing diagnostic challenges due to their nonspecific clinical presentation and similar features to those of other colorectal tumors. We present a case of a 61-year-old female with defecation accompanied by blood clots, initially diagnosed with a suspected tumor in the sigmoid colon. Despite initial biopsy yielding non-informative material, repeat colonoscopy and imaging studies revealed a malignant tumor with multinucleated giant (osteoclast-like) cells and probable p53 mutation, most likely of mesenchymal origin. Robotic surgical resection was performed, and ultimately pathological examination refined the diagnosis as a malignant PEComa of the colon. This case demonstrates the importance of considering PEComa in the differential diagnosis of colonic tumors. Further research is needed to ascertain the clinical behavior and optimal treatment for colonic PEComas.